Enterococcus species in the oral cavity: Prevalence, virulence factors and antimicrobial susceptibility - Komiyama, Edson Yukio [UNESP]; Lepesqueur, Laura Soares Souto [UNESP]; Yassuda, Cinthia Gomes [UNESP]; Samaranayake, Lakshman P.; Parahitiyawa, Nipuna B.; Balducci, Ivan [UNESP]; Koga-Ito, Cristiane Yumi [UNESP] (Public Library of Science (PLoS), 2016)
Enterococci are considered as transient constituent components of the oral microbiome that may cause a variety of oral and systemic infections. As there is sparse data on the oral enterococcal prevalence, we evaluated the Enterococcus spp. and their virulence attributes including antimicrobial resistance in a healthy Brazilian cohort. A total of 240 individuals in different age groups were studied (children 4-11 yrs, adolescents 12-17 yrs, young adults 18-29 yrs, adults 30-59 yrs, elderly over 60 yrs). Oral rinses were collected and isolates were identified by API 20 Strep and confirmed by 16S rDNA sequencing. E. faecalis isolates, in particular, were evaluated for virulence attributes such as their biofilm formation potential, and susceptibility to antimicrobials and an antiseptic, chlorhexidine gluconate. A total of 40 individuals (16.6%) and 10% children, 4% adolescents, 14% young adults, 30% adults, and 25% elderly carried oral enterococci. The oral enterococcal burden in adolescents was significantly lower than in the adults (p = 0.000) and elderly (p = 0.004). The proportion of carriers was higher among females (p = 0.001). E. faecalis was the most frequent isolate in all the age groups (p = 0.000), followed by E. durans and E. faecium.Whilst all the clinical isolates were able to form biofilms, only a proportion of them were able to produce lipase (92%), hemolysin (38%), and gelatinase (39%). Of all the isolates 53.8% were resistant to tetracycline, 12.3% to amoxicillin, 16.0% to ampicillin, 20.8% to chloramphenicol and 43.4% to erythromycin. None of the isolates were resistant to vancomycin. Our data suggest that in this Brazilian cohort the oral cavity may act as a significant reservoir of rather virulent and antibiotic resistant enterococci, with an increasing degree of carriage in the adults and elderly. Hence clinicians should be cognizant of this silent reservoir of virulent enterococci that may pose a particular threat of nosocomial infection.